A proposal for teaching SCADA systems using Virtual Industrial Plants in Engineering Education. Issue 6 (2016) - Rodríguez, F.; Guzmán, J.L.; Castilla, M.; Sánchez-Molina, J.A.; Berenguel, M.
Abstract: The main objectives of SCADA (Supervisory Control And Data Acquisition) systems are the supervisory analysis of the system, control algorithms validation, and data acquisition. These systems are normally implemented according to the international standards: UNE-EN ISO 9241, ISAIOI-Human-Machine Interfaces, ISA S5, and in the case treated in this paper The Spanish Royal Decree 488/1997. This paper presents a software architecture for the development of educational laboratories, through industrial virtual plants which models and logic are implemented in Matlab® and used within LabVIEW® through an appropriate protocol. Lab VIEW® from National Instruments, a specific purpose software for this kind of applications, was used, since it allows us to provide a friendly interface, to perform communications, data acquisition and the information management. In addition, to illustrate the use of the proposed architecture, different virtual industrial plants for students of different Bachelor and Master degrees in engineering at the University of Almeria have been developed. This paper shows the different virtual industrial plants that have been developed using SCADA systems to facilitate students' learning of basic concepts and techniques for an Industrial Informatics course.